Association between immune-related adverse event timing and treatment outcomes. (31st December 2022) - Hsiehchen, David; Naqash, Abdul Rafeh; Espinoza, Magdalena; Von Itzstein, Mitchell S.; Cortellini, Alessio; Ricciuti, Biagio; Owen, Dwight H.; Laharwal, Mehak; Toi, Yukihiro; Burke, Michael; Xie, Yang; Gerber, David E.
ABSTRACT: The timing of immune-related adverse events (irAE) associated with immune checkpoint inhibitors (ICI) is highly variable. Although the development of irAE has been associated with ICI clinical benefit, how irAE timing influences this association is unknown. We analyzed two independent cohorts including 154 patients with non-small cell lung cancer (NSCLC) treated with PD-1/PD-L1 inhibitors at a single institution (UTSW cohort) and a multi-center cohort of 433 patients with NSCLC who received second-line anti-PD-1/PD-L1 therapy (Global cohort) to assess the association between ICI outcomes and irAE timing. In both cohorts, late-onset irAE occurring more than 3 months after ICI initiation compared to irAE occurring earlier were associated with greater rates of radiographic response (UTSW cohort, 41% versus 28%, P = .26; Global cohort, 60% versus 35%, P = .02), longer progression-free (UTSW cohort, 13.7 versus 5.6 months, P < .01; Global cohort, not reached versus 6.0 months, P < .01) and overall survival (UTSW cohort, 30.9 versus 14.6 months, P < .01; Global cohort, not reached versus 10.6 months, P < .01). Modified landmark analysis at 6 months confirmed an overall survival difference between early- and late-onset irAE. Late-onset irAE was similarly associated with greater response rates and prolonged survival in a cohort of 130 patients with non-NSCLC malignancies, suggesting a conserved association across tumor types. The favorable association between irAE and ICI clinical outcomes may be attributed to later-onset events, which is not wholly explained by survivor bias. These results allude to a distinct biology between early- and late-onset irAE and may guide clinician expectations and thresholds for continuing or modifying immunotherapy.